Percepção dos estudantes de medicina sobre o uso da metodologia da problematização durante a graduação - Santiago, Rejane de Carvalho (2020)
The National curriculum guidelines (NCG) for medical graduation state that the course should be centered on the student as the subject of learning, with the professor as a facilitator and mediator of the process, with a view to full professional training. Medicine courses must use methodologies that favor student participation in the construction of knowledge. The aim of this study was to understand the medical student's perception about the problematization methodology in the Competence Integrating Problem (CIP) unit of the Pontifical Catholic University of Goiás (PUC Goiás). This is a cross-sectional descriptive study with a qualitative approach, which seeks to understand the context where the phenomenon occurs, centered on the qualitative deepening of the discourses produced by students. Data were collected through a semi-structured interview that used a previously prepared script of themes. Interviews were made with thirty academics from the first to the twelfth modules about the unit called Integrating Competence Problem (CIP), which is developed through the problematization methodology together with the insertion of the Charles Maguerez Arch. For data analysis it was used the Grounded Theory or Grounded Theory. With the results obtained after carrying out the transcription and analysis of the interviews, it was possible to create explanatory categories of the investigated phenomenon, they were: Previous knowledge of active methods; Impact and adaptation to the CIP; Positives, negatives and improvements; Characteristics of the student in the CIP; Characteristics of the professor in the CIP; CIP contributions to medical training. The present study showed the efficiency and the contributions of the functionality and applicability of the problematization methodology in the CIP unit, such as: communication skills, research, problem solving, proactivity, how to work in a team, how to listen and respect the opinion of colleagues, they became more critical and learned to see the patient holistically, for medical formation. As a new methodology inserted in the field of medical education, there are weaknesses both in the training of the student and in the performance of the mediator professor, such as such as dispersions that were not carried out or carried out without reaching the objectives, the neglect of both students and professors, the lack of preparation of some professors, the workload of the curricular matrix, and the recurrent absences of professors. Through the correct applicability of the problematization methodology, it becomes feasible to train medical professionals who have a holistic view, who do not treat only the disease but the human being in an integral way.